Acute effects of alcohol on cardiac electrophysiology and arrhythmogenesis: Insights from multiscale in silico analyses - Sutanto, Henry; Cluitmans, Matthijs J M; Dobrev, Dobromir; Volders, Paul G A; Bébarová, Markéta; Heijman, Jordi (Journal of Molecular and Cellular Cardiology, 2020)
Acute excessive ethyl alcohol (ethanol) consumption alters cardiac electrophysiology and can evoke cardiac arrhythmias, e.g., in 'holiday heart syndrome'. Ethanol acutely modulates numerous targets in cardiomyocytes, including ion channels, Ca2+-handling proteins and gap junctions. However, the mechanisms underlying ethanol-induced arrhythmogenesis remain incompletely understood and difficult to study experimentally due to the multiple electrophysiological targets involved and their potential interactions with preexisting electrophysiological or structural substrates. Here, we employed cellular- and tissue-level in-silico analyses to characterize the acute effects of ethanol on cardiac electrophysiology and arrhythmogenesis. Acute electrophysiological effects of ethanol were incorporated into human atrial and ventricular cardiomyocyte computer models: reduced INa, ICa,L, Ito, IKr and IKur, dual effects on IK1 and IK,ACh (inhibition at low and augmentation at high concentrations), and increased INCX and SR Ca2+ leak. Multiscale simulations in the absence or presence of preexistent atrial fibrillation or heart-failure-related remodeling demonstrated that low ethanol concentrations prolonged atrial action-potential duration (APD) without effects on ventricular APD. Conversely, high ethanol concentrations abbreviated atrial APD and prolonged ventricular APD. High ethanol concentrations promoted reentry in tissue simulations, but the extent of reentry promotion was dependent on the presence of altered intercellular coupling, and the degree, type, and pattern of fibrosis. Taken together, these data provide novel mechanistic insight into the potential proarrhythmic interactions between a preexisting substrate and acute changes in cardiac electrophysiology. In particular, acute ethanol exposure has concentration-dependent electrophysiological effects that differ between atria and ventricles, and between healthy and diseased hearts. Low concentrations of ethanol can have anti-fibrillatory effects in atria, whereas high concentrations promote the inducibility and maintenance of reentrant atrial and ventricular arrhythmias, supporting a role for limiting alcohol intake as part of cardiac arrhythmia management.
Keywords: Gap Junctions; Heart; ethanol; počítačová simulace; Myocytes, Cardiac; Action Potentials; Fibrosis; srdeční síně; srdce; mezerový spoj; lidé; Arrhythmias, Cardiac; Ethanol; Computer Simulation; remodelace cév; iontové kanály; Ion Channels; elektrofyziologické jevy; Heart Atria; Vascular Remodeling; Electrophysiological Phenomena; fibróza; srdeční arytmie; akční potenciály; kardiomyocyty; Humans